Colour Changes in Blanc de Noir Wines during Ageing at Different Temperatures and its Colour Preference Limits - Ellis, L.P.; Kok, C. (South African Journal of Enology and Viticulture, 2017)
Visual as well as spectrophotometrically measured colour changes were studied in six blanc de noir wines during ageing at 0, 10, 20°C and 30°C. Visual colour descriptions were compared with spectrophotometric measurements of absorbance at 420 nm and 520 nm, in order to obtain colour preference limits for this type of wine. A limit where the spectrophotometrically measured absorbance values at 420 nm and 520 nm do not exceed 0,200 and 0,160 respectively, was found best suited for this purpose. The results showed that the colour of blanc de noir wine is susceptible to change during ageing. This deterioration of colour quality during ageing occurred especially in wines which initially had a more intense colour. High temperatures during ageing have a detrimental effect on the retention of colour quality.